Building Ethical Business: Islam's Contribution to Facing Modern Economic Challenges - Ika Hartika; Masruri Masruri; Nurhikmah Nurhikmah; Sitti Aisya (Pt. Anagata Sembagi Education, 2025)
This study aims to examine the contribution of Islamic business ethics in facing modern economic challenges and how these ethical principles can help build ethical businesses. The method used is Systematic Literature Review (SLR), which aims to identify, evaluate, and synthesize findings from literature relevant to this topic. The first step is to formulate research questions related to modern economic challenges and the contribution of Islamic business ethics. Next, relevant literature is selected with inclusion and exclusion criteria, and then analyzed to provide a deep understanding of the solutions offered by Islam. The results of the study show that Islamic business ethics emphasizes moral principles such as honesty (ṣidq), justice ('adl), amanah, and social responsibility. Business in an Islamic perspective is not only oriented towards material profit, but also aims to obtain blessings and social welfare. These principles prohibit detrimental practices such as usury, gharar, and maysir, and encourage the implementation of zakat, infaq, and waqf to overcome economic inequality. In addition, the application of sharia principles in modern business, as applied by sharia fintech and halal marketplace, shows that businesses can operate ethically and have a positive impact on society. Thus, this study underlines the importance of implementing Islamic business ethics to create sustainable, ethical, and fair businesses, as well as a relevant model for public policy in facing global economic challenges.